2007
DOI: 10.1177/1352458506073647
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction and sympathetic skin response recorded from the genital region in women with multiple sclerosis

Abstract: Multiple Sclerosis is known to cause autonomic and sexual dysfunction. However, genitourinary and sexual problems in female multiple sclerosis patients are difficult to analyse. Therefore, it is an understudied field. As an attempt to fill this gap, we evaluated genital region autonomic dysfunction of female multiple sclerosis patients by using genital sympathetic skin response. Forty female patients with definite multiple sclerosis and twenty healthy female controls were included in the study. We examined han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…This finding is consistent with several previous studies showing that SP are a prevalent squeal in women with MS [3,10]. The total score of MSISQ-19 was 48.1, indicating a higher score than in the studies of Demirkiran et al, Celik et al and Yeliz et al [3,4,23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with several previous studies showing that SP are a prevalent squeal in women with MS [3,10]. The total score of MSISQ-19 was 48.1, indicating a higher score than in the studies of Demirkiran et al, Celik et al and Yeliz et al [3,4,23].…”
Section: Discussionsupporting
confidence: 92%
“…Studies on sexual dysfunction in patients with MS report a wide range of frequencies between 40%-80% in women and 50%-90% in men [4-7]. Almost half (47%) of American women [8] and 61% of Israeli women [9] had sexual dysfunction, while in Turkey, the majority of women (75-80.1%) reported sexual dysfunction [3,10]. …”
Section: Background and Objectivesmentioning
confidence: 99%
“…Demirkiran et al [14] determined that primary SD had developed in 80.4% of MS patients. Oskay et al [27] found the sexual dysfunction rate of female fertile groups as 42.9%, while the Seçil et al [15] study results showed the sexual dysfunction rate as 75%. However, when compared to other studies, our own study results showed a lower rate of dysfunction at 27.1%.…”
Section: Discussionmentioning
confidence: 95%
“…Hulter and Lundberg's study [35] with female MS patients found that urinary bladder and intestinal problems, changes in lubrication and decreasing desire and capacity were related to vertigo and changes in the senses. The Seçil et al [15] study stated that there is no statistical relation between EDSS and sexual dysfunction, yet when the severity of the disease increases, the number of complaints of SD due to disability, depression, and partner irritability increases as well. Sevene et al [36] stated that motor, sensorial, bladder, intestinal problems, cognitive problems and spasms negatively affect the sexual lives of MS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation